The Development of a Sustainability-Oriented Creativity, Innovation, and Entrepreneurship Education Framework: A Perspective Study - Shu, Yu; Ho, Shin-Jia; Huang, Tien-Chi (Frontiers in Psychology, 2020)
Innovation can include creativity, innovation mechanisms, and entrepreneurship. The ability to innovate is an important indicator of economic and social development, and creativity is an educational indicator of learning effectiveness. This article explores creativity and innovation from an educational perspective and proposes a sustainability-oriented creativity, innovation, and entrepreneurship education framework that uses creative problem solving. This framework contains four layers and three dimensions. The first layer concerns the thinker and basic structure, and the second layer contains the catalyst of sustainable development goals (SDGs). The third layer is the advanced structure of cultivating SDG thinkers. The final layer is the generation of students who will attempt to start up social enterprises. The three aspects apply the creative nature of diffuse thinking to social innovation; applies demand expansion to extend individual needs to societal needs; applies educational goal development to encourage sustainability. We expect this framework, which can turn thinkers into doers through creativity and social innovation, to apply to different disciplines. This article provides suggestions for (1) designing curriculum in creativity, innovation and entrepreneurship education (CIE) for different education level, (2) transitioning technical and vocational education in developing economies on the road to sustainable development.